Extreme energy poverty in the urban peripheries of Romania and Israel: Policy, planning and infrastructure. (August 2020) - Teschner, Naama; Sinea, Anca; Vornicu, Andreea; Abu-Hamed, Tareq; Negev, Maya
Abstract: Extreme energy poverty results from a mix of conditions including lack of access to a reliable and affordable grid-based energy source that meets basic domestic needs. In this paper, we focus on two communities that face multiple complications regarding modern energy and housing infrastructure: Roma neighborhoods in Romania and Bedouin villages in Israel. Our goal is threefold: to map within the two national contexts existing norms, policies and regulation with references to energy poverty; to identify and analyze the main characteristics and challenges associated with extreme energy poverty; finally, to highlight and discuss the nexus of infrastructure, planning and social inequality from the perspective of energy provision. Research methods included regulatory and policy analysis as well as interviews with policy and decision-makers in both countries. We found that, in both national contexts, laws and policies avoid a clear definition of energy poverty, instructions on how to measure it, and a systematic collection of relevant data. At the same time, there are no long-term policies to tackle energy poverty at a national scale. The study also found that policymakers perceive extreme energy vulnerability to be less urgent than other challenges for these excluded communities, and that long-lasting mistrust is a prominent characteristic of extreme energy conditions, as we define for the first time. Our additional contribution is conceptual: we show how informal housing conditions are combined with additional spheres of informalities, and how informal coping strategies with the challenge of energy poverty may be adopted by policymakers.